The political rationality of restorative justice. (November 2019) - Maglione, Giuseppe
This article investigates the political conditions that have enabled the development of restorative justice, in England and Wales, over the last 40 years. By applying a governmentality approach, it conceptualizes the emergence of restorative justice as a response to distinctive political problematics, enacted by a range of governmental technologies and driven by a combination of competing political rationalities. In so doing, the article seeks to shed light on the assemblage of ambivalent principles and values that constitute restorative justice by linking them to conflicting political contingencies. This could have implications in understanding both the fragmentary growth of restorative justice in England and Wales, and, more generally, the political roots of restorative justice policies, programmes and practices beyond the British borders.